Stability analysis and design of model predictive reset control for nonlinear time-delay systems with application to a two-stage chemical reactor system. (November 2018) - Pourdehi, Shabnam; Karimaghaee, Paknosh
Highlights: A systematic Lyapunov-based approach for reset control of nonlinear time-delay system is proposed. A model predictive strategy is proposed to design the reset law. Based on Lyapunov–Krasovskii approach, the reset controller is synthesized. The control problem of a two-stage chemical reactor with delayed recycle streams is considered. Abstract: This paper presents a systematic Lyapunov-based approach for reset control of nonlinear time-delay system. The reset controller consists of a base controller and a reset law that enforces resets to the controller states. The reset actions are triggered if predefined reset conditions are satisfied and reset law is used to determine reset values of the controller states. A model predictive strategy is proposed to design the reset law by solving a linear matrix inequality optimization problem. Based on Lyapunov–Krasovskii approach, the reset controller with guaranteed asymptotical stability is synthesized. Finally, we apply the developed method to the control design of a two-stage chemical reactor with delayed recycle streams, and the simulation results verify the effectiveness of the main results.